Why economics textbooks should, but don't, and won't, change - David Colander (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
The standard textbook presentation of many policy issues, such as the financial crisis and income distribution, is problematic. This view is shared by many economists, both mainstream and heterodox. Despite this agreement, it has not and will not change because the textbook presentations have become institutionalized, and are intricately connected to the existing institutional structure. This paper explains why that is the case, arguing that we should not expect the economics profession to exhibit a composite rationality as economists focus on local incentives tied to existing institutional structures. It discusses how presenting policy within a complexity frame may make it more likely that, if the stars align just right, change will be more likely.
Keywords: A2; B4; B5; 330; complexity; teaching; principles of economics; textbooks; heterodox